Inheritance of high-density grain index in an upland rice (Oryza sativa) cross - CHAUHAN, J C (The Indian Journal of Agricultural Sciences, 2013)
The components of gene effects for high-density grain index were studied in a cross 'Khaolo 33' x 'Kalinga III' of rice (Oryza sativa L.) following 5- parameter model of Hayman, utilizing means of P1, P2, F1, F2 and F3 generations. The high-density grain index showed high heterobeltiosis along with high inbreeding depression, indicating the role ofdominance gene action in the inheritance of this trait. The additive and dominance interactions were important, but thischaracter was largely governed by non-additive gene action. Complementary epistasis was prevalent. The preponderanceof dominance x dominance type of gene effect restricts the scope of early-generation selection. The progeny selection in F3 or F4 generation may be useful for the improvement of this character, whose association with grain weight, size and shape was not consistent in F2 and F3 generations.